Material and Digital Reconstruction of Fragmentary Dead Sea Scrolls : The Case of 4Q418a - Ben-Dov, Jonathan (Studies on the Texts of the Desert of Judah, 2022)
This book presents an innovative and comprehensive method for reconstructing fragmentary scrolls in a digital environment. The method enables extracting maximum information from the fragments. It is exemplified on the scroll 4Q418a, a fragmentary copy of Instruction.